Temporal Evolution in Patient-Reported Outcomes in Indian Women With Breast Cancer: A Longitudinal Study - Suman Ghosh; Tabassum Wadasadawala; Sanjay Mohanty; Rajiv Sarin; Vani Parmar; Sudeep Gupta (JCO Global Oncology)
PURPOSEBreast cancer (BC) is the most common malignancy among women in India and globally. Given the high survivorship, understanding the evolution of health-related quality of life (HRQoL) is crucial, yet comprehensive longitudinal studies from India are lacking.PATIENTS AND METHODSThis prospective observational study included 500 patients with BC registered between June 2019 and March 2022. HRQoL was assessed at pretreatment, treatment completion, and 6-month follow-up using European Organisation for Research and Treatment of Cancer (EORTC)-QLQ-C30, EORTC-QLQ-BR-23, and EQ-5D-5L tools. A linear mixed-effects model analyzed HRQoL trajectories and predictors.RESULTSThe median patient age was 46 years, with 60.8% presenting with locally advanced disease; all patients underwent multimodal therapy, comprising surgery (57% mastectomy), chemotherapy (95%), and radiotherapy (RT; 77%). Pretreatment global QoL scores were influenced by age (younger fared better, P = .003), stage (P = .027), and social displacement (P = .038). Longitudinal assessment revealed a small decline in global QoL (–2.1) and EQ-VAS (–1.9), along with meaningful improvements in social (+12.8), cognitive (+4.3), and role function (+7.3). Symptom burden significantly decreased, except for deterioration in body image (–7) and sexual enjoyment (–16). Younger patients had slower recovery in physical (P = .003) and social function (P = .05), while school education and financial independence positively influenced QoL variation. Social displacement affected trajectories of QoL (P = .017), role (P = .032), and social function (P = .024). Extent of surgery and RT did not affect overall HRQoL trends, although RT recipients reported more fatigue (P = .029).CONCLUSIONTo our knowledge, this is the first longitudinal HRQoL study in Indian patients with BC, showing significant improvement in most functional domains at early survivorship. Sociodemographic factors, such as age, social displacement, education, and financial independence, rather than treatment modalities, were stronger predictors of HRQoL. Longer follow-up is needed for a more comprehensive assessment.